Spirits on the Crossing - Travellers to/from Nowhere : Contemporary Art in Canada 1980-94. - Nemiroff, Diana; Kohmoto, Shinji; Hasegawa, Yuko; The National Museum of Modern Art, Kyoto; Hokkaido Museum of Modern Art, Sapporo (Tokyo : Setegaya Art Museum, 1995)
Cadieux, Geneviève ; Douglas, Stan ; Frenkel, Vera ; Graham, Rodney ; Grauerholz, Angela ; Steinman, Barbara ; Sterbak, Jana ; Wall, Jeff ; Wodiczko, Krzysztof
Spirits on the Crossing - Travellers to/from Nowhere : Contemporary Art in Canada 1980-94, Setagaya Art Museum, Setagaya, January 28 - March 26, 1995 ; The National Museum of Modern Art, Kyoto, April 11 - May 14, 1995 ; Hokkaido Museum of Modern Art, Sapporo May 24 - July 5, 1995
English-Japanese
kunstcatalogus
Keywords: Canada